Global health diplomacy in Mexico: insights from key actors in the field - German Guerra; Emanuel Orozco; Paulina Jiménez; Arne Ruckert; Ronald Labonté; Nelly Salgado de Snyder (BMC, 2021)
Abstract Background Global health diplomacy (GHD) focuses on the actions taken by diverse stakeholders from different nations -governments, multilateral agents, and civil society- to phenomena that can affect population health and its determinants beyond national borders. Although the literature on conceptual advancements of GHD exists, empirical studies about how health becomes an issue of relevance for foreign policy are scarce. We present an analysis of the entry processes of health into the foreign policy and diplomatic domains in Mexico from the perspective of key informants of three different sectors. Methods A purposive sample of high-rank representatives of three sectors involved in GHD was designed: Two from Health Sector (HS), four from Foreign Affairs Sector (FAS), and three from Non-governmental organizations (NGOs). Nine semi-structured interviews were conducted exploring the topics of: (1) Health concerns entering diplomatic and foreign policy; (2) Processes that allow actors to influence foreign policy and negotiation and; (3) Impact of multilateral negotiations on decision-making at the national level. Results Our analysis suggests that GHD in Mexico is hierarchically driven by the FAS and health concerns only enter foreign policy when they are relevant to national priorities (such as trade or security). HS possesses a lesser degree of influence in GHD, serving as an instance of consultation for the FAS when deciding on health-related issues at global meetings (i.e., World Health Assembly). NGOs resort to lobbying, advocacy, networking, and coalition-working practices with other sectors (academy, think-tanks) to prevent harmful impacts on local health from multilateral decisions and as a mean to compensate its power asymmetry for influencing GHD processes in relation to the government. Conclusions GHD in Mexico occurs in a context of asymmetric power relationships where government actors have the strongest influence. However, NGOs' experience in raising awareness of health risks needs to be weighted by government decision-makers. This situation calls for capacity building on intersectoral communication and coordination to create formal mechanisms of GHD practices, including the professionalization and training on GHD among government agencies.